Haemoglobin Levels in Early Pregnancy and Severe Maternal Morbidity: Population-based Cohort Study. Issue 2 (24th June 2021) - Ray, J.G.; Davidson, A.J.F.; Berger, H.; Dayan, N.; Parka, A.L.
Abstract : ( BJOG . 2020;127:1154–1164) Globally, 38% of all pregnancies are affected by anemia, which has been associated with poor perinatal outcomes including low infant birthweight, perinatal asphyxia, preterm birth, and stillbirth. Identifying this condition early may allow for prediction of severe maternal morbidity (SMM). The aim of this study was to identify the relationship between early maternal hemoglobin concentration and SMM, blood transfusion, or maternal mortality.